2020
DOI: 10.3892/ijmm.2020.4669
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin‑induced oxidative and nitrosative stress: Mitochondrial connexin 43 is at the crossroads

Abstract: Oxidative stress is widely accepted as a key factor of doxorubicin (doxo)-induced cardiotoxicity. There is evidence to indicate that nitrosative stress is involved in this process, and that doxo interacts by amplifying cell damage. Mitochondrial connexin 43 (mitocx43) can confer cardioprotective effects through the reduction of mitochondrial reactive oxygen species production during doxo-induced cardiotoxicity. The present study aimed to evaluate the involvement of mitocx43 in doxo-induced nitrosative stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…In this regard, it has been shown that pharmacological inhibition of Hsp90 with radicicol, a treatment reducing mitochondrial Cx43 expression in H9c2 cardiomyoblasts, increased cardiotoxicity to doxorubicin, as determined by an enhancement in doxorubicin-induced ROS production, in mitochondrial calcium overload and in cytochrome C release [ 535 ]. Additionally, an increase in nitrosative stress was also observed after radicicol treatment [ 558 ]. Similar findings have been obtained with trastuzumab, the gold standard in the treatment of HER2+ breast cancer [ 559 ].…”
Section: Cardiac Connexinsmentioning
confidence: 99%
“…In this regard, it has been shown that pharmacological inhibition of Hsp90 with radicicol, a treatment reducing mitochondrial Cx43 expression in H9c2 cardiomyoblasts, increased cardiotoxicity to doxorubicin, as determined by an enhancement in doxorubicin-induced ROS production, in mitochondrial calcium overload and in cytochrome C release [ 535 ]. Additionally, an increase in nitrosative stress was also observed after radicicol treatment [ 558 ]. Similar findings have been obtained with trastuzumab, the gold standard in the treatment of HER2+ breast cancer [ 559 ].…”
Section: Cardiac Connexinsmentioning
confidence: 99%
“…Transmembrane Cx43 contributes to cell–cell communication and electrical coupling by the formation of gap junction channels, while on the mitochondrial membrane Cx43 exists as a hemichannel and is involved in mitochondrial volume regulation and respiration [ 6 ]. During stress conditions, Cx43 translocates to the mitochondria with a mechanism that involves the Hsp90/Tom20 machinery system [ 4 , 7 ], and many studies conducted using the Hsp90 inhibitor radicicol supported this theory [ 8 , 9 , 10 ]. Mitochondrial Cx43 (mCx43) acts as an important regulator of apoptosis, allowing the passage of molecules that induce apoptosis such as Ca 2+ , IP 3 and cAMP ions [ 11 ] and influencing mitochondrial respiration, matrix ion fluxes and ROS production [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…During stress conditions, Cx43 translocates to the mitochondria with a mechanism that involves the Hsp90/Tom20 machinery system [ 4 , 7 ], and many studies conducted using the Hsp90 inhibitor radicicol supported this theory [ 8 , 9 , 10 ]. Mitochondrial Cx43 (mCx43) acts as an important regulator of apoptosis, allowing the passage of molecules that induce apoptosis such as Ca 2+ , IP 3 and cAMP ions [ 11 ] and influencing mitochondrial respiration, matrix ion fluxes and ROS production [ 9 ]. Indeed, mitochondria are at the same time the most powerful intracellular source and the primary target for damaging effects of ROS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we did not detect a significant increase in DSB markers in primordial oocytes after DOX or ETO treatment, suggesting a different mode of toxicity for these agents. It is possible that DOX induces late DNA damage in oocytes indirectly by increasing oxidative stress and reactive oxygen species (ROS) (80)(81)(82)(83). Indeed, co-administration of drugs reducing oxidative stress have been shown to decrease its ovotoxicity (84-86) and γH2AX-positive oocytes were reported after in vivo treatment with DOX (57,87).…”
Section: Discussionmentioning
confidence: 99%